A Case Report of Reconstruction of the Left Superior Vena Cava Using the Right Superior Vena Cava Autograft at Bilateral Bidirectional Superior Cavopulmonary Anastomosis. Issue 4 (July 2020) - Shiraishi, Shuichi; Sugimoto, Ai; Moon, Jiyong; Takahashi, Masashi; Tsuchida, Masanori
The choice of graft material for reconstruction of the vena cava in pediatric patients remains controversial. We successfully treated an eight-month-old female patient with single ventricle physiology and long segment obstruction of the left superior vena cava using the right superior vena cava autograft at the time of bilateral bidirectional superior cavopulmonary anastomosis. Postoperative computed tomography confirmed the patency of the reconstruction.